Optimized syntheses of Fmoc azido amino acids for the preparation of azidopeptides - Pícha, Jan; Buděšínský, Miloš; Macháčková, Kateřina; Collinsová, Michaela; Jiráček, Jiří (Journal of peptide science, 2017)
The rise of CuI-catalyzed click chemistry has initiated an increased demand for azido and alkyne derivatives of amino acid as precursors for the synthesis of clicked peptides. However, the use of azido and alkyne amino acids in peptide chemistry is complicated by their high cost. For this reason, we investigated the possibility of the in-house preparation of a set of five Fmoc azido amino acids: β-azido l-alanine and d-alanine, γ-azido l-homoalanine, δ-azido l-ornithine and ω-azido l-lysine. We investigated several reaction pathways described in the literature, suggested several improvements and proposed several alternative routes for the synthesis of these compounds in high purity. Here, we demonstrate that multigram quantities of these Fmoc azido amino acids can be prepared within a week or two and at user-friendly costs. We also incorporated these azido amino acids into several model tripeptides, and we observed the formation of a new elimination product of the azido moiety upon conditions of prolonged couplings with 2-(1H-benzotriazol-1-yl)-1,1,3,3-tetramethyluronium hexafluorophosphate/DIPEA. We hope that our detailed synthetic protocols will inspire some peptide chemists to prepare these Fmoc azido acids in their laboratories and will assist them in avoiding the too extensive costs of azidopeptide syntheses. Experimental procedures and/or analytical data for compounds 3-5, 20, 25, 26, 30 and 43-47 are provided in the supporting information. © 2017 The Authors Journal of Peptide Science published by European Peptide Society and John Wiley & Sons Ltd.
Keywords: močovina; Azides; Fluorenes; Alkynes; Urea; alkyny; ethylaminy; Click Chemistry; aminokyseliny; triazoly; Peptides; azidy; Amino Acids; click chemie; fluoreny; Triazoles; Ethylamines; peptidy